Female pseudohermaphroditism due to classical 21-hydroxylase deficiency and insulin resistance in a girl with Turner syndrome - Atabek, M Emre; Kurtoğlu, Selim; Keskin, Mehmet (The Turkish Journal of Pediatrics, 2005)
We report five-year-old girl with female pseudohermaphroditism due to classical form of 21-hydroxylase deficiency associated with Turner’s syndrome (45,X/46,XX) and insulin resistance. She had clitoromegaly since birth, but Turner’s syndrome and 21-hydroxylase deficiency were diagnosed incidentally at one and five years of age, respectively. Moreover, we determined insulin resistance, which resolved following corticosteroid therapy for disease. We regard the rare combination as a coincidental occurrence. We stress that adrenal function should be assessed, at least in the presence of clitoral enlargement, in patients with Turner’s syndrome, particularly if their karyotype does not contain a Y chromosome. We conclude that chronic hypersecretion of androgen precursors due to an inborn error of metabolism can induce a reduction in insulin sensitivity. Improvement in insulin resistance after treatment of hyperandrogenism has not been previously reported.